Exergy-based optimization of direct conversion of microalgae biomass to biodiesel. (10th January 2017) - Karimi, Mahmoud
Abstract: In order to comply with criteria of green energy concepts and sustainability, a new procedure has been performed for ultrasound-assisted in-situ transesterification of microalgae slurry to extract lipids and convert to biodiesel. Response surface methodology and artificial neural networks, followed by multiple response optimization using desirability function approach, were applied to individually and simultaneously evaluate fatty acid methyl ester (FAME) yield and exergy efficiency in process of the in-situ transesterification. Ultrasonic power, reaction time and concentrations of methanol and chloroform in oil were considered as the design variables in maximizing FAME content and exergy efficiency. The maximum individual desirability of FAME content was predicted to be 87.68% corresponding to an ultrasonic power of 150 W, reaction time of 100 min, methanol:oil molar ratio of 83 and chloroform:oil molar ratio of 97. Based on the simultaneous optimization of exergy efficiency and FAME content, the most overall desirability was determined at an ultrasonic power of 137 W, reaction time of 100 min, molar ratios of methanol to oil of 83 and chloroform to oil of 30 to achieve FAME content of 81.2% and exergy efficiency of 79.8%, respectively. Graphical abstract: Image 1 Highlights: Biodiesel yield and exergy efficiency were used as a decision-making tool. Yield increased significantly with increasing ultrasound intensity and time. Ultrasound irradiation could significantly enhance exergy efficiency. Extra concentration of solvents reduced exergy efficiency. In-Situ Transesterification could be optimized using artificial neural networks.